The Product Life Cycle and the Export Position of the United States - Lutz, James M.; Green, Robert T. (Journal of International Business Studies, 1983)
The present study analyzed trade in 4-digit level manufacturing categories over time for 4 nations, including the United States, to ascertain the relevance of the product life cycle theory of such trade. The level of technological input was controlled for. The result indicate that the theory has at least some explanatory relevance for 3 of the 4 countries, including the United States.